Automated analysis of chloride and nitrate ions in the wastewaters by ionometry; 11th International Forum on Strategic Technology (IFOST 2016); Pt. 1 - Vtorushina A. N. Anna Nikolaevna; Larionova E. V. Ekaterina Vladimirovna; Basharova A. Y. Aleksandra Yurjevna; Bulygina K. A. Kseniya Andreevna (2016, 2016)
Title screen